Portal Thrombosis: Clinical, Etiological and Therapeutic Aspects in the Hepato-Gastroenterology - Maliha Saad, Sayad Ahmad, Azhar Saeed, Shafqat Ur Rehman Orakzai, Mushtaq Muhammad, Amanullah Khokhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Our study aimed to assess the frequency of PT, outline its clinical and etiological manifestations, and detail its therapeutic therapy in the field of hepato-gastroenterology. Study Design: Retrospective study Place and Duration: In the department of Medicine and Gastroenterology of Ayub Teaching Hospital Abbottabad and HBS Dental and General Hospital, Islamabad for the duration of six months from June 2021 to November 2021. Methods: There were 94 patients of both genders had symptomatic gastro abnormalities included in this study. After getting informed written consent detailed demographics of enrolled cases were recorded. Patients were underwent for CT scan and ultrasound for image examination. Prevalence, etiology, therapeutic and clinical aspects of PT were assessed. SPSS 22.0 was used to analyze all data. Results: The mean age of the patients was 40.3±8.60 years and had mean BMI 24.4±6.30 kg/m2. There were majority males 53 (56.4%) and 41 (43.6%) females. Majority were from urban areas. Most common symptoms were abdominal pain, ascites and gastrointestinal bleeding. Prevalence of PT was found in 3 (3.2%) cases. Majority patients 65 (69.1%) were diagnosed with ultrasound and 29 (30.9%) patients received CT scan of abdomen. Frequency of complete thrombosis was found in 63 (67.02%) cases. Most common etiology was cirrhosis followed by hepatocellular carcinoma. Conclusion: According to the findings of our study, the prevalence of PT in hepato-gastroenterology is 3.2%. Cirrhosis exacerbated by HCC is the principal cause of the chronic form, which has a very high prevalence rate. Keywords: Cirrhosis, Hepatocellular Carcinoma, Portal Thrombosis